Model Data Warehouse dan Business Intelligence untuk Meningkatkan Penjualan pada PT. S - Rudy Rudy; Natalia Limantara (Bina Nusantara University, 2011)
Today a lot of companies use information system in every business activity. Every transaction is stored electronically in the database transaction. The transactional database does not help much to assist the executives in making strategic decisions to improve the company competitiveness. The objective of this research is to analyze the operational database system and the information needed by the management to design a data warehouse model which fits the executive information needs in PT. S. The research method uses the Nine-Step Methodology data warehouse design by Ralph Kimball. The result is a data warehouse featuring business intelligence applications to display information of historical data in tables, graphs, pivot tables, and dashboards and has several points of view for the management. This research concludes that a data warehouse which combines multiple database transactions with business intelligence application can help executives to understand the reports in order to accelerate decision-making processes.